Vibration characteristic investigation on distribution transformer influenced by DC magnetic bias based on motion transmission model. (June 2018) - Liu, Xingmou; Yang, Yongming; Huang, Yichen; Jadoon, Ammad
Highlights: A model and method for vibration transmission of transformer is proposed. The magnetic and deformation distribution in transformer is obtained. A test system is designed and built to collect the vibration signals of transformer. The odd harmonics of transformer vibration in different locations all increases. The amplitude ratios of vibration signals could be confirmed by fitting curve. Abstract: Transformer is an important equipment for power energy transmission. The vibration and noise of transformer have always been a serious issue of people concern. Transformer body vibration and noise are mainly caused by the global magnetization of limbs and yokes and magnetic forces of transformer core. However, the process of vibration transfer from core to body is a key factor for monitoring the transformer condition. In this paper, a transformer model for vibration transmission is presented based on motion transmission and it can be used to analyze the vibration relation between core and shell of transformer. Considering strain of silicon steel as the vibration source, the motion equations whichexpress the relations of transformer core and shell are derived. And then, the test system is built to analyze the vibrations of a 5 kVA three phase transformer. A 3D real model simulation used COMSOL finite element software is performed for analyzing the deformation characteristic of transformer. The locations of test points which reflect the vibration more efficiently are determined through the deformation simulation results. Lastly, the vibration signals of two directions have been measured considering DC magnetic bias or not. The experimental results reveal that vibration relations between core and shell are satisfied with the theoretical derivation. Therefore, the Vibration Transmission is significant and it can provide valid method for the DC magnetic bias analysis and core diagnosis of transformer.